Evaluation of maxillary anterior teeth proportion with Chu’s Gauge in a population of Central India: an in-vivo study - Wagh, Sukhada Arun; Mantri, Sneha S.; Bhasin, Abhilasha (Medicine and Pharmacy Reports, 2020)
Aim. To evaluate the width/height proportions in maxillary anterior natural dentition and its correlation with Chu’s esthetic proportion Gauge. Settings and Design. Observational cross-sectional study with the inclusion criteria of well aligned maxillary anterior teeth. Purpose. The present study attempts to perceive the application of Chu’s Esthetic Proportion Gauge in a group of the central Indian population . Methods. A total number of 150 participants within the age group 18- 30 years were screened, out of which 80 participants were selected, who fulfilled the inclusion criteria of well aligned maxillary anterior teeth with pleasing smile, unrestored, periodontally sound, no fracture, no missing, absence of diastema teeth and no H/O orthodontic treatment. The selected participants were seated on the dental chair with the Frankforts horizontal plane parallel to the floor. The participants were observed for height and width proportions using the Chu’s esthetic proportion gauge and measured using digital vernier calliper. The proportion and measured height and width ratios were then compared . Results. The recorded data was compiled and entered in a spreadsheet computer program (Microsoft Excel 2007) and then exported to data editor page of SPSS version 20.0 (SPSS Inc., Chicago, Illinois, USA). Intergroup comparison between gauge and vernier caliper was done using Chi- square test for proportions percentages (Qualitative data) and Mann-Whitney U test of width and height and then categorized into esthetic and unesthetic anterior teeth. Level of significance was set at 0.05. Conclusions. Within the limitations of the study, it was concluded that maxillary anterior teeth did show similarity with Chu’s esthetic proportion scale.